Uncovering Stunting Prevention through the Important Role of Posyandu Cadres - Anisyah, Dewi; Fitria Agustina, Isna (Indonesian Journal of Public Policy Review, 2024)
This study analyzes the role of posyandu cadres in preventing stunting in Cangkring Village, Malang, Beji District, Pasuruan Regency, using a descriptive qualitative approach. Data were gathered through interviews, observation, and documentation from village heads, posyandu cadres, midwives, and mothers of toddlers. Utilizing Lawrence Green's framework, the findings reveal that stunting prevention is hindered by limited parental knowledge (Predisposing Factors), inadequate health facilities (Enabling Factors), and low community awareness (Reinforcing Factors). The research highlights the need for better education, improved facilities, and stronger community and governmental support to enhance posyandu effectiveness in stunting prevention. Highlights: 1. Knowledge Gap: Parental knowledge about stunting is insufficient.2. Infrastructure: Health facilities are inadequate and poorly maintained.3. Community Support: Low public awareness reduces posyandu effectiveness. Keywords: Posyandu cadres, stunting prevention, rural health, qualitative research, community health